Diagnostic Utility of Ultrasonography for Duodenal Ulcers in Pediatric Cases in Japan - Sakata, Yasufumi; Yasudo, Hiroki; Uchida, Masashi; Saito, Mitsuru; Azuma, Yoshihiro; Hasegawa, Shunji (Frontiers in Pediatrics, 2020)
Objective: To evaluate the diagnostic utility of wall hypertrophy of the duodenal bulb with a hyperechoic lumen, designated as the “HH sign,” using ultrasound sonography (US) in pediatric duodenal ulcer (DU) patients. Study design: We performed a US for five pediatric subjects diagnosed with DU by upper gastroscopy to determine the presence of the potentially diagnostic HH sign. The sonographic images were analyzed before and after DU treatment. Computed tomography was performed in three cases and fecal occult blood test (FOBT) in all five cases. Results: Upper gastroscopy confirmed DU in all patients. While the HH sign was observed using US in four cases, with the DU located in the anterior bulb, the FOBT was positive in only one case. In these four cases, the HH sign diminished in response to treatment, as visualized by US. This was observed for both the initial as well as recurrent episodes. A mass-like region was observed in only one case, with the ulcer located in the proximity of the inferior duodenal wall. Conclusion: The HH sign is useful for the follow-up of DU, and US may be a suitable modality for the follow-up. We believe that this diagnostic marker can aid in following up a greater number of DU cases.